2017
DOI: 10.5897/ajmr2016.8340
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and molecular identification of newly isolated pigmented bacterium and improved production of biosurfactant

Abstract: A novel bacterium pigmented isolate from Caatinga soil was characterized by biochemical and molecular assays, as well as, by rep-polymerase chain reaction (PCR) and 16S rDNA sequencing, and was identified as Serratia marcescens based on 99% of similarity. The identity of the sequences were compared by pairs of critical species of S. marcescens found in National Center for Biotechnology Information (NCBI) with a 96% homology of the isolated species to species database. The wild strain was able to produce biosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Previously, Araújo et al [25] used the same substrates and FFD for the production of biosurfactant by S. marcescens UCP 1549, but in static conditions, and they found the best results in condition 8, with reduction on surface tension to 30.60 mN/m. Highest tensioactive activity detected in current study in flasks with agitation can be linked to the physiological function of the biosurfactants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Araújo et al [25] used the same substrates and FFD for the production of biosurfactant by S. marcescens UCP 1549, but in static conditions, and they found the best results in condition 8, with reduction on surface tension to 30.60 mN/m. Highest tensioactive activity detected in current study in flasks with agitation can be linked to the physiological function of the biosurfactants.…”
Section: Resultsmentioning
confidence: 99%
“…In other hand, it was ratified the suitability of CWW as low-cost substrate for biosurfactant production. Commonly, it is used as nitrogen source, because it has a high presence of nitrogen in its composition [8, 25, 33, 34] (see Additional file 1: Table S1). Earlier, Ferraz et al [33] showed the ability of the biosurfactant produced by S. marcescens to reduce water surface tension of 72–28 mN/m using CWW as substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If this trash is not managed well, it may cause problems for the environment. Nonetheless, creative methods have surfaced to transform this waste into useful goods, such as the synthesis of biosurfactants ( Helvia et al, 2017 ). Fruit peels, pulps, and seeds are among the many waste products produced by the fruit processing industry.…”
Section: Types Of Sources Used For Biosurfactant Productionmentioning
confidence: 99%